2012
DOI: 10.1155/2012/157643
|View full text |Cite
|
Sign up to set email alerts
|

Application of Statistical Design for the Production of Cellulase by Trichoderma reesei Using Mango Peel

Abstract: Optimization of the culture medium for cellulase production using Trichoderma reesei was carried out. The optimization of cellulase production using mango peel as substrate was performed with statistical methodology based on experimental designs. The screening of nine nutrients for their influence on cellulase production is achieved using Plackett-Burman design. Avicel, soybean cake flour, KH2PO4, and CoCl2 ·6H2O were selected based on their positive influence on cellulase production. The composition of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…The predicted R 2 value of 0.9532 is in reasonable agreement with the adjusted R 2 of 0.9838 and the difference between the two is <0.2. Adequate precision measured value of 37.235 indicates an adequate signal and the model were navigated in the design space left%Crtrue(VItrue)removal = +96.101.29 × dose0.56 × pH + 6.06 × contact time3.61 × Initial Crtrue(VItrue)conc0.47 × dose × pH0.45 × dose × contact time + 0.15 × dose × initial Crtrue(VItrue) conc + 0.085 × pH × contact time + 0.52 × pH × initial Crtrue(VItrue) conc + 0.60 × contact time × initial Crtrue(VItrue) conc 4.83 × dose28.59 × pH2 2.11 × contact time22.18 × initial Crtrue(VItrue) conc2 …”
Section: Resultsmentioning
confidence: 99%
“…The predicted R 2 value of 0.9532 is in reasonable agreement with the adjusted R 2 of 0.9838 and the difference between the two is <0.2. Adequate precision measured value of 37.235 indicates an adequate signal and the model were navigated in the design space left%Crtrue(VItrue)removal = +96.101.29 × dose0.56 × pH + 6.06 × contact time3.61 × Initial Crtrue(VItrue)conc0.47 × dose × pH0.45 × dose × contact time + 0.15 × dose × initial Crtrue(VItrue) conc + 0.085 × pH × contact time + 0.52 × pH × initial Crtrue(VItrue) conc + 0.60 × contact time × initial Crtrue(VItrue) conc 4.83 × dose28.59 × pH2 2.11 × contact time22.18 × initial Crtrue(VItrue) conc2 …”
Section: Resultsmentioning
confidence: 99%
“…Обговорення. Останнім часом метод Плакетта-Бермана отримав широке розповсюдження для оптимізації умов синтезу екстрацелюлярних гідролаз [21]. Більшість досліджень показали позитивні результати, проте цей метод використовували, головним чином, для підвищення целюлазної активності за одним з показників.…”
Section: таблиця 1 компоненти поживного середовища в матриці плакеттаunclassified
“…Since mango peel is a rich source (10-15%) of pectin, a complex set of polysaccharides, pectinase treatment can be effective for release of fermentable sugars. Saravanan et al (2012) have suggested alkaline pretreatment to decrease the crystallinity of mango peel and for simultaneous removal of lignin and other inhibitors. For pretreatment, 2% NaOH was added and autoclaved at 121°C for 30 min and excess alkali was neutralized with phosphoric acid.…”
Section: Biotechnological Potentialities Production Of Ethanolmentioning
confidence: 99%
“…Mango peel at the level of 7% (w/v) has been used for carboxymethyl cellulose (CMCase) production using Paenibacillus polymyxa (Kumar et al 2012a). Mango peel has been used for the production of cellulase enzyme (Saravanan et al 2012) and a maximum cellulase activity of 7.8 IU/mL was reported under optimized conditions.…”
Section: Wine Fermentationmentioning
confidence: 99%